Wielokulturowe stanowisko w Wysokiej, stan. 1, pow. łańcucki – wyniki badań sondażowych z 1995 roku (analiza obiektów nieruchomych i źródeł ceramicznych) - Adamik-Proksa, Joanna (Muzeum Okręgowe w Rzeszowie, 2022)
The aim of the article is to present and analyse immovable finds and ceramic materials of the Mierzanowice, Trzicniec and Tarnobrzeg Lusatian cultures collected from site No. 1 in Wysoka, coming from trial excavations carried out in 1995. The uncovered ceramics indicate typical characteristics of the late phase of the Mierzanowice culture, the classical stage of development of the Trzciniec culture and the oldest phase of the Tarnobrzeg Lusatian culture. Research results in Wysoka, site 1 has also provided very important data on the specificity of settlement in the area of the Rzeszów Foothills.

Site 1 in Wysoka has a relatively well-established position in the literature of the subject, where it is mainly recorded as a cemetery of the Tarnobrzeg Lusatian culture. This was due to the discovery of urns with burnt bones in the village in 1947. Later surface and excavation surveys (1952, 1961, 1983, 1985–1986), apart from the materials of this unit, also brought finds from older prehistoric periods and the Middle Ages. It turned out that site 1 in Wysoka should be perceived as a multicultural area. This state was confirmed by the first trial excavations (sondages) in this area, which were carried out by Wojciech Blajer in 1995. The aim of the article is to present and analyse the discoveries from the aforementioned excavation season. However, it should be noted here that this site was studied on a larger scale in 2001 (Paweł Madej, Wojciech Blajer), 2002 and 2004 (Paweł Madej). The trial excavations of the site in 1995 were carried out within 13 sondage trenches with a total area of 163 m 2 . Exploration units were located at regular intervals within an area of approximately 120×70 m (Fig. 2). In the course of excavation research, traces of quite advanced erosion were recorded in the studied area. In the western part of the site (sondages VI and XII – Fig. 8:6–7; 14:1–2), the subsoil level was reached immediately after removal of the topsoil (at a depth of approx. 30 cm). In other sectors, the loess subsoil appeared only at a depth of 90 cm or even 120 cm (sondages I, IA, II, IIA, III – Fig. 6:1–5; 7:1–5; 8:1–2). Stratigraphic sections through the site also document the presence of cultural layers – a dark grey layer, filled with artefacts (Fig. 6:1–3; 7:1–5; 8:2; 11:1–2; 12:1–4; 13:1–3; 15:1). In addition, there was barren, almost black hard soil recorded under the cultural layer in the eastern part of the studied area. The research carried out in 1995 led to the discovery of over a dozen immovable features and numerous movable artefacts at site 1 in Wysoka – ceramics (about 1300 pottery sherds), flint tools and flint and stone waste. They confirm the occupation of the site in the period corresponding to the following cultures: Mierzanowice (hereinafter KM), Trzciniec (hereinafter TC), Tarnobrzeg Lusatian culture (hereinafter TLC), and probably also units developing in the periods of Roman influence, Early Middle Ages and Modern period. KM materials constitute the largest group of sources – seven immovable features, over 500 pottery sherds and a relatively large series of flint artefacts. All features assigned to KM are trapezoidal pits (No. 2, 4, 5, 9, 10 – Fig. 9:1–2, 3; 10:2–3; 11:2–3; 13:6–7; 14:3–4). Only one of these structures has been fully explored (feature No. 2); others only partially. These are quite deep pits (feature 2 – 180, feature 4 – 235, feature 5 – 200, feature 9 – 178, feature 10 – 220). Their diameter ranges from 258 cm (feature 2 – Fig. 9:1–2,4) to 350 cm (feature 9 – Fig. 14:3–4). In all features of this type, a similar character of the fill was also observed – layered. The collection of ceramic materials attributed to KM consists of 503 pieces. It is dominated by thin-walled ceramics, made of clay thinned with a fine admixture of white granite stone grit, sometimes supplemented with chamotte, limestone or black hornstone. With reference to pottery forms, it is also worth mentioning pots (e.g. Table I:1,9,11–12; II:8), cups (Table I:3; II:3,6,10,15), amphorae (Table I:1,13) and bowls (Table II:14). Regarding the ornamentation, an impressed decoration of cord is dominated, sometimes quite developed (Table I:2–3,5,7,10–11,14; II:1–3,5–7,9,14–15). In many cases they represent horizontal rows of single or double bands, vertical impressions or loops (Table I:3; II:6). These motifs are often accompanied by plastic knobs (e.g. Table I:11; II:1) or stamp impressions (Table II:2,14). Plastic knobs are usually located below the edge of the rim, in the upper parts of the necks (e.g. Tables I:1, 8; II:1,4,8). Additionally, many pottery sherds wear traces of textile or pseudo-textile imprints. Another characteristic stylistic decoration used on the vessels from Wysoka is the so-called Besenstrichmuster, i.e. smeared with a broom. Generally speaking, in the collection of KM materials from the 1995 survey, there are mainly references to the stylistics of the late phase of the Mierzanowice culture, mainly the Samborzec group. In addition, it is worth noting that the discussed set is distinguished from the indicated group by certain specific features. It is reflected primarily in the results of rescue surveys in 2001, 2002 and 2004, nevertheless it is also noticeable at other sites in the Rzeszów Foothills (including Boratyn, site 17, Kańczuga, site 5, Sietesz, site 5 – main pit 15). All aforementioned complexes are characterized by very frequent use of textile roughening, the presence of triangular stamp impressions and unique technology. The second, more distinct settlement episode at site 1 in Wysoka is represented by TC, to which only four pits and a collection of 410 pottery sherds have been identified. TC features include: storage pits (features No. 6 and 7), which are definitely smaller and shallower than storage pits from the Early Bronze Age. It is also possible to include features 1 and 11 to this group of pits affiliated to the mentioned unit (Fig. 4:1; 6:5; 15:2–3) – shallow structures with basin-shaped profiles and uniform fills. The pottery of this culture is carefully made – smoothed. For its production, clay thinned with stone grit of fine or medium grains was used. Regarding the entire collection, edge fragments stand out against the background, sometimes preserved together with the belly parts, or fragments from the middle parts of poorly profiled vessels (e.g. Table III:1,2; IV:2–3,12,23). At least some of them can probably be combined with the group of “classic” gently profiled pots of the Trzciniec culture. During the excavations carried out at the site, a large number of characteristic edge fragments were also found (Table III:3–6,8,10–11,14,17,19,20; IV:1,4,7,8,10,11,13,16,21–22, 24) and decorated pottery sherds (Table III:2,9,11,13,15,16,18,19,21–22; IV:2–3,6,9,12,14,16–20, 23). Speaking of the ornamentation of the Trzciniec vessels uncovered at the site in Wysoka, it is represented by horizontal motifs, made with the incised or plastic technique. Their exclusive participation clearly indicates the chronology within the so-called classical phase. During the trial trench excavations at site No. 1 in Wysoka, few examples of TLC materials were also discovered. The stage of settlement of the site associated with the discussed unit is represented by only one feature (pit No. 8) and a poor collection of pottery (130 fragments). The documented pit had a round shape in the horizontal outline, while its profile was trapezoidal, with a clear multi-layer structure, and it was about 120 cm deep. The collection of pottery sherds assigned to the TLC is represented by two relatively well-preserved pots from feature No. 8 and several dozen small, mostly uncharacteristic sherds from sondage trenches located in the southern sector of the analysed area. In terms of technology, it is a fairly homogeneous collection. It is dominated by ceramics with brown surfaces (group III – 62%), most often with a rough texture (74%). Regarding the admixture, a significant share of crashed pottery sherds (chamotte) is visible. As for the uncovered vessels and their fragments, there are few forms characteristic of a specific stage of evelopment of the mentioned cultural unit. Only two tulip-shaped pots can be used as date indicators (Table V:1,4). This form is very common at the sites of the first phase of the TLC development. In addition, trial excavations at site 1 in Wysoka, apart from the discovery of the sources of KM, TC and TLC, also provided few and usually very small ceramic fragments from the Neolithic, Roman, Medieval and Modern periods. These materials were deposited in various parts of the site within the cultural layer. Most of them, however, were out of context; they were recorded on the surface of the site, within the arable land or in the excavated area.
Multicultural site in Wysoka, site 1, Łańcut District – results of trial excavations from 1995 (an analysis of immovable finds and ceramic artefacts)
Keywords: Bronze Age; Mierzanowice culture; Trzciniec culture; Tarnobrzeg Lusatian culture; settlement archeology